2001
DOI: 10.2174/0929867013372111
|View full text |Cite
|
Sign up to set email alerts
|

Non-Peptidic Prenyltransferase Inhibitors: Diverse Structural Classes and Surprising Anti-Cancer Mechanisms

Abstract: The development of farnesyltransferase inhibitors (FTIs) has been one of the most active areas of anticancer drug development for the past ten years. This review presents a general overview of the developments in this area, along with a critical appraisal of the anticancer activity of FTIs. A historical survey of the protein prenylation field is given, in particular to emphasize the key role played by the Ras oncoprotein in driving the discovery of prenyltransferase enzymes. The different classes of prenylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 147 publications
(216 reference statements)
0
41
0
Order By: Relevance
“…[29][30][31][32][33][34] The peptidomimetic compound L-778,123 has undergone clinical testing. 35 Several FTIs have been reported to be competitive with the farnesyl diphosphate substrate 36 or are bisubstrate analogs incorporating structural features of both farnesyl diphosphate and the CAAX tetrapeptide. 37 Other FTIs were identified by screening of chemical libraries followed by medicinal chemistry optimization, including the tricyclic compound SCH 66336 and its analogs, 38,39 R115777, 40 and BMS-214662.…”
Section: Preclinical Activity Of Ftismentioning
confidence: 99%
“…[29][30][31][32][33][34] The peptidomimetic compound L-778,123 has undergone clinical testing. 35 Several FTIs have been reported to be competitive with the farnesyl diphosphate substrate 36 or are bisubstrate analogs incorporating structural features of both farnesyl diphosphate and the CAAX tetrapeptide. 37 Other FTIs were identified by screening of chemical libraries followed by medicinal chemistry optimization, including the tricyclic compound SCH 66336 and its analogs, 38,39 R115777, 40 and BMS-214662.…”
Section: Preclinical Activity Of Ftismentioning
confidence: 99%
“…This membrane attachment requires numerous post-translational modifications. The initial step is the covalent addition of a 15C far- jpet.aspetjournals.org nesyl or a 20C geranylgeranyl group to the cysteine located on the C-terminal CaaX box (Gibbs et al, 2001). This modification is critical for proper Ras function and has been investigated as a potential target for treating NF1 MPNST cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ras proteins are translated as inactive precursor molecules that must undergo a series of post-translational modifications before becoming fully functional (Gibbs et al, 2001). The first necessary step is the covalent addition of a prenyl group, either a 15C farnesyl or a 20C geranylgeranyl group, to the C-terminal "CaaX" box (Basso et al, 2006).…”
mentioning
confidence: 99%
“…Based on this result, we started designing non-peptidic compounds as the FTI since the peptide bonds and carboxyl group of 1 do not appear to play an important role for the binding activity other than conformational bias for proper placement of hydrophobic side chains. 6 We designed a non-peptidyl structure with amino-thiol group and hydrophobic group connected through a rigid spacer as shown in figure 1 based on the assumption that the peptide bonds adopt extended conformation for enzyme binding.…”
mentioning
confidence: 99%
“…The binding activity of A 16 that can be viewed as ring constrained benzyl or reduced naphthyl group indicated that restriction of conformational freedom of the phenyl group of the A3 improved the binding activity by five fold while the reduction of an aromatic ring of A 14 to the cyclohexyl ring lowered the activity by ten fold. A polar group, especially the hydroxyl group attached to the naphthyl group interfered with the binding of the inhibitor (compounds A 6,17,19 ). All these results were in good agreement with the idea that these amide groups bind to the hydrophobic binding site created by the hole in the FTase and FPP bound to the enzyme.…”
mentioning
confidence: 99%